A Structuralist Narratological Analysis of Mohsin Hamid’s Novel The Last White Man - Anam, Sana; Ajmal, Muhammad; Sharif, Hafiz Rizwan (Annals of Human and Social Sciences, 2024)
This research article conducts a comprehensive Structuralist Narratological Analysis of Mohsin Hamid’s novel, The Last White Man. Employing the framework of structuralist theory, the study explores the intricate narrative structures and underlying patterns within the text, shedding light on the novel’s construction and the significance of its narrative elements. The analysis delves into the interplay of characters, plot, and discourse, unraveling the textual complexities that contribute to the overall meaning and aesthetic experience of the novel. By applying structuralist principles to The Last White Man, this research aims to deepen our understanding of the novel’s literary craftsmanship and thematic intricacies, offering valuable insights into Hamid’s narrative choices and their implications for the broader field of literary studies.